Case Report: Stress Fracture in an International Triple Jumper: Importance of an Integrated Care Approach Which Also Incorporates Biomechanics - Allado, Edem; Ankri, Marine; Khiami, Frédéric; Tamgho, Teddy; Hamroun, Aghiles; Proenca Lopes, Catarina; Poussel, Mathias; Chenuel, Bruno (Frontiers in Sports and Active Living, 2021)
Athletes fear stress fracture (SF) injuries as they can put a premature end to their athletic careers. Understanding any mechanical constraints can suggest preventive management approach. Specifically, for the triple jump, the mechanical stresses that occur during the event appear to be the main factors for risk of injury. This clinical case describes three successive episodes of anterior tibial fracture in an international triple jumper between 2011 and 2013. The first fracture received surgical treatment involving intramedullary nailing. The second fracture occurred in the same location and was considered a recurrence requiring medical treatment, whilst the third was a complete fracture of the surgical material and required surgical revision. These recurrent fractures can be explained by the fatigue of materials (bone and nail) induced by triple jump practice and emphasize the importance of integrating biomechanics into an assessment of the case. The use of biomechanical modelization to identify these weaknesses could be an approach for clinical management of such patients. Observation of the intrinsic mechanical stresses during high-level triple jump may lead to identification of modifiable risk factors for bone fragility.